DESIGN OF SECOND ORDER BUTTERWORTH HIGHPASS FILTER USING CMOS TECHNOLOGY - Anggraini Puspita Sari; Agung Darmawansyah; M Julius St (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
The research Complementary Metal-Oxide Semiconductor (CMOS) Technology for Design of second order butterworth highpass filter IC. This is caused CMOS have excellence low power dissipation and small size. This research aims to know performance, quality and reliability second order butterworth highpass filter circuit. The method used to problem solving, analysis with the literature and the simulation use pspice program for exam the specification of circuit. To make IC picture using DSCH software and layout circuit using Microwind program. From examination result -2,99dB for gain voltage parameter, frequency -40dB and 88,25° phase shift second order highpass filter. The result of this circuit have low power dissipation although applied to second order highpass filter equal 2,28mW better than generality IC second order highpass filter (GH580). Wide of layout circuit is 1110µm x 385µmDOI : https://doi.org/10.26905/jeemecs.v1i1.2299